Atividade antibacteriana in vitro e in vivo de Schinus terebinthifolius Raddi no controle da mastite bovina - Faccin, Ângela (2013)
The scientific interest in herbal medicine has led to the development of research based on the popular practices. This study aimed to evaluate the antibacterial activity of the hydroalcoholic extract and essential oil from the leaves and fruits of Schinus terebinthifolius Raddi at two growth stages against bacteria related to bovine mastitis, besides testing a plant extract with antibacterial action, to be used antisepsis in milking. The thesis is presented in two papers. The first refers to the in vitro antibacterial activity of hydroalcoholic extract and essential oil from leaves and fruits at two growth stages, tested by serial microdilution plates against bovine mastitis bacteria. The results were expressed as Minimal Bactericidal Concentration. All extracts showed antibacterial activity. The second paper shows results for the in vivo experiment, which tested the hydroalcoholic extract of the leaves of the plant before and after dipping for twelve consecutive weeks, was used as control iodine commercial, weekly data were collected regarding clinical mastitis, subclinical and new intramammary infections, and biweekly health data sphincter and skin from the ceiling. None of the indices analyzed apresentraram difference between treatments, suggesting that the plant extract can be used to teat antisepsis as a replacement of conventional products. In our study we have obtained satisfactory results from the use of this plant, it has antibacterial activity against bacteria in bovine mastitis and teat disinfection has similar results to the conventional product.